Integration of Industry 4.0 Concepts into Lean Six Sigma Projects: A Case Study in the Ready-Mixed Concrete Industry - Droguett-Villalobos, T (Springer Nature, 2025)
This paper presents a case study for the achievement of operational excellence in a company branch dedicated to the production and distribution of ready-mix concrete. Lean Six Sigma (LSS) methodology is selected to carry out the objective by following the DMAIC stages. The main quality attribute for customer satisfaction is product docility upon delivery at customer’s site, which is related to the water/cement ratio of the mixture. For this, the focus is placed on quality deviations within the production and transportation cycle. The deviations in the tolerance of the unloaded product and the performance indicators were measured to construct a regression model to find the main process variables affecting variations. In the Improvement stage, it is implemented a new process control system with GPS, water flow sensors installed at the mixer trucks and an APP for the driver to help control the process by regulating the mixer pressure and the amount of water to keep the docility of the product while in movement. Over a period of six months, an improvement of the main performance indicators was achieved. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.